KOTAK INFAK DI NU-CARE LAZISNU KABUPATEN SRAGEN: IMPLEMENTASI DAN PENGELOLAAN - Huda, Miftahul; Kasanah, Nur (Al-Syakhsiyyah: Journal of Law & Family Studies, 2019)
AbstractPhilanthropy is all voluntary activities of individuals and communities, both in the form of objects and services used for public purposes. Philanthropy has a broader range of meanings than charity. In Islam, philanthropy can be in the form of zakat, donation, alms, and endowments. In Sragen Regency, Central Java, the local Nahdlatul Ulama (NU) through the NU Amil Zakat Institute is known as the NU Care LAZISNU initiated the realization of Islamic philanthropy which is unique namely, philanthropic activity based on infaq coins or coins called the NU Coin Movement, this paper shows that the implementation of the management of the NU Coin Movement in NU Care LAZISNU Sragen Regency consists of fund-raising management, distribution management, and utilization and reporting management has progressed well as modern management as evidenced by the results of distribution to the people who need it.Keywords: Philanthropy, Alms giving, Waqf, Charity AbstrakFilantropi adalah semua kegiatan pemberian sukarela dari individu dan masyarakat, baik berupa benda maupun layanan yang digunakan untuk kepentingan umum. Filantropi memiliki cakupan makna yang lebih luas dari amal (charity). Dalam Islam, filantropi dapat berupa zakat, infak, sedekah dan wakaf. Di Kabupaten Sragen Jawa Tengah, Nahdlatul Ulama (NU) setempat melalui Lembaga Amil Zakat NU yang dikenal dengan nama NU Care LAZISNU menginisiasi terwujudnya filantropi Islam yang cukup unik yaitu, aktivitas filantropi berbasis kotak infak uang koin atau receh yang disebut Gerakan Koin NU, tulisan ini menunjukkan bahwa pelaksanaan manajemen Gerakan Koin NU di NU Care LAZISNU Kabupaten Sragen terdiri dari manajemen fundraising, manajemen distribusi dan pendayagunaan dan manajemen pelaporan telah berkembang dengan baik sebagaimana menejemen modern yang dibuktikan dengan hasil penyaluran kepada masyarakat yang memerlukan.